Efek Mediasi Kepercayaan pada Pengaruh Persepsi Manfaat dan Persepsi Kemudahan terhadap Minat menggunakan e-Money - Syahrina, Aulia; Christiana, Irma (Jurnal Ilmu Manajemen, 2023)
This study aims to analyze the effect of perceived benefits and perceived convenience on interest in using e-money, with trust as an intervening variable in generation Z. The method used in this research is a quantitative descriptive approach. The population in this study was 3,875 students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara, while the sample research method used the Slovin formula, so that a sample of 100 people was obtained. Methods of data collection using a questionnaire While the data analysis technique uses the statistical path analysis model, namely the partial least squares structural equation model (PLSSEM), The results showed that perceived benefits and perceived convenience had a significant effect on trust. Furthermore, perceived benefits have a significant effect on the intention to use e-money, while perceived convenience has no significant effect on the intention to use e-money. Trust has a significant effect on interest in using e-money. Trust is able to mediate the effect of perceived benefits on interest in using e-money, but is unable to mediate the effect of perceived ease of use on interest in using e-money.